2006
DOI: 10.1121/1.2169923
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical determination of the parameters governing viscous dissipation in porous media

Abstract: Analytical solutions are derived to extract from dynamic density the macroscopic parameters governing viscous dissipation of sound waves in open-cell porous media. While dynamic density is obtained from acoustical techniques, the analytical solutions are derived from the model describing this dynamic density. Here, semiphenomenological models by Johnson et al. and by Wilson are investigated. Assuming dynamic density, open porosity, and static airflow resistivity known, analytical solutions derived from the Joh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(105 citation statements)
references
References 23 publications
2
100
0
3
Order By: Relevance
“…In this situation, the experimentally measured effective density and effective bulk modulus could be used to quantify a 1 , K, K 0 , and k 0 0 from analytical inversion, 25,26 if one directly measures the porosity / and the permeability k 0 . 27 As rigid-frame behavior cannot be completely assumed here (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this situation, the experimentally measured effective density and effective bulk modulus could be used to quantify a 1 , K, K 0 , and k 0 0 from analytical inversion, 25,26 if one directly measures the porosity / and the permeability k 0 . 27 As rigid-frame behavior cannot be completely assumed here (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that these two models are sufficiently robust to be used in the parameter inversion process, which is based on the optimisation procedure applied to the surface impedance data or using the numerical approach. 22,39,40 The flow resistivity and other parameters determined from the inversion process can be used to estimate the size of particles that composed the material skeleton and size of pores, which can be important for a number of non-acoustic applications.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 These procedures require accurate data on the dynamic density ρ b (ω) and complex compressibility C b (ω), which are not often easy to measure. As a result, a number of other inversion methods have been proposed to determine the non-acoustical parameters of complex porous media from acoustical data for the absorption coefficient and surface impedance spectra.…”
Section: Optimisation Methods For Parameter Inversionmentioning
confidence: 99%
“…21 The two characteristic lengths (K, K 0 ) and the thermal permeability k 0 0 are determined using the indirect characterization method proposed by Panneton and Olny. 22,23 This requires the measurement of the equivalent dynamic bulk modulus K eq ¼ K=U and equivalent dynamic density q eq ¼ q=U of the tested material performed here using the 3-microphone impedance tube method proposed by Salissou and Panneton. 24 The indirect method associated to the 3-microphone impedance tube method has been recently detailed by the authors in Ref.…”
Section: -3mentioning
confidence: 99%